Comparison of Density of States of Fermi Gas and Bose-Einstein Condensate in Single Valence Electron Bulk Metal Elements (Global Journal of Science Frontier Research, 2018)
The density of states of Fermi gas and density of states of Cooper pairs that form Boson Condensate have been compared. The derived density of states of Fermi gas is elucidated using literature in a cube of size L [1]. In this line, Cooper pairs are highly coherent and responsible for super conductivity[2]. The Cooper pairs form Boson-Einstein condensate of spin quantum number s-1[3], we obtained its density of states. The ratio of Cooper pair density of states to Fermi gas density of states has been derived. To obtain the relation between the two densities of states, the condition of high coherent Cooper pairs in Bose-Einstein condensate has been taken in to account. In addition, the fact that Fermions do not take same quantum states was employed while highly coherent Cooper pairs with s-1 do take same quantum states for they are Boson particles.
Keywords: density of states; fermi gas; cooper pairs; bose-einstein condensate